Glucosylsphingosine is a potential fluid-based biomarker of lysosomal dysfunction in Cln3Δex7/8 mice - Hallie Wald; Stephanie Cicalese; Lihang Yao; Nathan Hatcher; Weiwei Luo; Xiaolan Shen; Xiaoli Ping; Brie Culp; Dan Metzger; Mark Ault; Christian Nunes; Mali Cosden; et al. (Neurobiology of Disease, 2025)
CLN3 disease is a rare fatal juvenile neurodegenerative lysosomal storage disease. Challenges in tracking underlying disease biology have hindered the identification of effective therapeutic targets and the ability to execute clinical trials in this rare disease. While diagnostic biomarkers are readily available, biomarkers that reflect the underlying core lysosome dysfunction are lacking. In the present study, CLN3Δex7/8 iPSC derived models were used to link hallmark cellular pathology and lysosomal parameters at the cellular level to potential novel biomarkers. A Cln3Δex7/8 disease mouse model was used to link established clinical diagnostic biomarkers and hallmark cellular pathology to novel biomarkers in tissue and biofluid in-vivo. Non-invasive retinal imaging modalities were used to identify the established visual dysfunction in the Cln3Δex7/8 disease mouse model. These techniques better characterize significant and progressive retinal layer degeneration, bipolar cell dysfunction, and autofluorescent aggregate deposition in Cln3Δex7/8 mice. Retinal imaging biomarkers also coincided with an increase in ATP synthase subunit C, a hallmark disease pathology, in the retina and brain. Additionally, quantitative lipidomic analyses of brain, retina and plasma specimens from Cln3Δex7/8 mice identified alterations in levels of lysosomally-regulated sphingolipid species including marked accumulation of the Gaucher Disease biomarker glucosylsphingosine 18:1 (GlcSph). Sphingolipid concentrations were measured in CLN3Δex7/8 iPSC-derived neural progenitor cells and cortical neurons. CLN3Δex7/8 iPSCs exhibited marked elevation of GlcSph which coincided with hallmark accumulation in ATP synthase subunit C levels as well as reduced cellular lysosomal content and enzymatic function. The in vivo and in vitro data link alterations in established non-invasive clinical retinal biomarkers, hallmark subunit c accumulation and defects in lysosomal health to the accumulation of GlcSph. Taken together, these findings hold promise for future development of GlcSph as a potential biomarker of lysosomal function in CLN3 disease.